Customary Law as a Pathway to Social Justice: A Comparative Analysis of Corporate Social Responsibility and Performance Requirements in Indonesian and Vietnamese Foreign Investment Frameworks - Arifin, Miftah; Arifin, Zainal; Widiastuti, Anna; Ismanto, Hadi; Giang, Vu Le (Faculty of Law, Universitas Pattimura, 2026)
Introduction: Economic globalization has strengthened foreign investment flows in developing countries such as Indonesia and Vietnam. However, investment policy orientations that overemphasize economic efficiency often ignore social justice for local communities. This inequality raises the need to revisit the legal framework that governs the relationship between foreign investors and the recipient community. Customary law is seen as a source of values and moral principles that can strengthen social legitimacy in the practice of foreign direct investment (FDI).Purposes of the Research: This study aims to analyze how customary law can play a role in restoring social justice through the implementation of corporate social responsibility (CSR) and performance requirements in foreign investment, by comparing the legal frameworks of Indonesia and Vietnam, this study seeks to find a model of customary law integration that is able to balance economic interests with the social and cultural values of local communities.Methods of the Research: This study uses a normative-comparative legal approach by analyzing laws and regulations, policy documents, and CSR implementation practices in Indonesia and Vietnam. Data was collected through literature studies and content analysis of various primary and secondary legal sources. A comparative approach is used to identify similarities and differences in the application of customary law as the basis for foreign investment policies in both countries.Results of the Research: The results of the study show that Indonesia has adopted customary law principles, such as mutual cooperation and social justice, within the legal framework of CSR and investment performance requirements. In contrast, Vietnam still emphasizes socialist state policies without explicit recognition of local customary law values. The integration of customary law has been proven to strengthen the social legitimacy and sustainability of investments, as it fosters corporate social responsibility that is in line with community values and promotes more equitable and inclusive development.